Bias free multiobjective active learning for materials design and discovery - Kevin Maik Jablonka (Nature Portfolio, 2021)
Identifying optimal materials in multiobjective optimization problems represents a challenge for new materials design approaches. Here the authors develop an active-learning algorithm to optimize the Pareto-optimal solutions successfully applied to the in silico polymer design for a dispersant-based application.